Moral Agents and Their Deserts : The Character of Mu'tazilite Ethics - Vasalou, Sophia (Book collections on Project MUSE., 2008)
Must good deeds be rewarded and wrongdoers punished? Would God be unjust if He failed to punish and reward? And what is it about good or evil actions and moral identity that might generate such necessities? These were some of the vital religious and philosophical questions that eighth- and ninth-century Mu'tazilite theologians and their sophisticated successors attempted to answer, giving rise to a distinctive ethical position and one of the most prominent and controversial intellectual trends in medieval Islam. The Mu'tazilites developed a view of ethics whose distinguishing features were its.